(NpO^WY NOWYH ZEMELX (BIII-(NGO SOWHOZA (B((NpAKARSKOGO(B) /s - d; (NsELXSKOHOZQJSTWENNYJ tREST nARKOMZEMA ssras ((N|RIWANX (B:s (Nb(B. (NI(B. ,s, 1930)
(NrEZ(B.: (NANGL(B.s
Keywords: (NpO^WYs -- (NaRMENIQs -- (NpARAKARs